Survival outcome of women with stage IV uterine carcinosarcoma who received neoadjuvant chemotherapy followed by surgery. Issue 3 (16th October 2017) - Matsuo, Koji; Johnson, Marian S.; Im, Dwight D.; Ross, Malcolm S.; Bush, Stephen H.; Yunokawa, Mayu; Blake, Erin A.; Takano, Tadao; Klobocista, Merieme M.; Hasegawa, Kosei; Ueda, Yutaka; Shida, Masako; et al.
Abstract : Background and Objectives: To examine survival of women with stage IV uterine carcinosarcoma (UCS) who received neoadjuvant chemotherapy followed by hysterectomy. Methods: This is a nested case‐control study within a retrospective cohort of 1192 UCS cases. Women who received neoadjuvant chemotherapy followed by hysterectomy based‐surgery for stage IV UCS ( n  = 26) were compared to those who had primary hysterectomy‐based surgery without neoadjuvant chemotherapy for stage IV UCS ( n  = 120). Progression‐free survival (PFS) and cause‐specific survival (CSS) were examined. Results: The most common regimen for neoadjuvant chemotherapy was carboplatin/paclitaxel (53.8%). Median number of neoadjuvant chemotherapy cycles was 4. PFS was similar between the neoadjuvant chemotherapy group and the primary surgery group (unadjusted‐hazard ratio [HR] 1.19, 95% confidence interval [CI] 0.75‐1.89, P  = 0.45). Similarly, CSS was comparable between the two groups (unadjusted‐HR 1.13, 95%CI 0.68‐1.90, P  = 0.64). When the types of neoadjuvant chemotherapy regimens were compared, women who received a carboplatin/paclitaxel regimen had better survival outcomes compared to those who received other regimens: PFS, unadjusted‐HR 0.38, 95%CI 0.15‐0.93, P  = 0.027; and CSS, unadjusted‐HR 0.21, 95%CI 0.07‐0.61, P  = 0.002. Conclusion: Our study found that there is no statistically significant difference in survival between women with stage IV UCS who are tolerated neoadjuvant chemotherapy and those who undergo primary surgery.